“Rigid criteria should not be established”? A history of peer evaluation in European humanities funding - Verbergt, Marie-Gabrielle (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
This article asks when, how, and why external peer review was introduced in the funding procedures of the European Science Foundation’s Standing Committee for the Humanities. It covers both the period before and after the introduction of external review in 1997. Up to then, a lack of selection criteria in combination with highly flexible procedures made it possible for a small elite to allocate funding based on personal convictions and ties. When peer review was introduced, this was done not only because of ideological reasons, but also for logistical, and, in the end, economic reasons. This insight challenges all too triumphant interpretations of the history of peer review and points to the intricate connection of the history of peer review to scale and institutional changes in European research policy.